Scrutiny of residual nitrogen content and different nozzle designs on NOx formation during oxy-fuel combustion of natural gas. (1st October 2020) - Schluckner, C.; Gaber, C.; Demuth, M.; Hochenauer, C.
Highlights: Investigating the NOx emissions of natural gas combustion during oxy-fuel operation. Accurate NOx emission prediction for different oxy-fuel burner and nozzle designs. Simulations provided information of the flame shape and the NO formation region. Accurate NOx emission prediction for oxidizers containing up to 10%v N2 in O2 . Abstract: The aim of this work is to investigate and improve the understanding of the complex processes involved in NOx formation during oxy-fuel combustion of natural gas. In this study, two industrial non-premixed jet burner designs were experimentally and numerically analyzed for their sensitivity on NOx formation during the combustion of natural gas with pure oxygen and mixtures containing up to 10 % v nitrogen in oxygen. The two burners differed by their design: (1) a high-momentum co-axial burner with changeable nozzle designs, and (2) a low-momentum fish-tail burner. The study revealed that the high-momentum burner design outperformed the fish-tail burner during operation in similar operating points since at 1320 ° C the NOx emissions could be reduced by 60% using 10 % v N 2 in oxygen as oxidizer and decreased by 75% during pure oxy-fuel combustion. At 1320 ° C, the NOx emissions could thus be reduced from 858 to 339 mg kWh - 1 ( 3 % v O 2 reference on a dry basis) using 10 % v N 2 in oxygen as oxidizer and could be lowered from 215 to 51 mg kWh - 1 during oxy-fuel combustion. In addition to the experiments, a fast-solving computational fluid dynamics (CFD) model, representing the experimental setups, was developed to analyze NOx formation. Steady-state simulations including a multi-step skeletal mechanism applicable for oxy-fuel combustion were conducted and the NOx emissions were calculated in a post-processing step. A mixture fraction-based model (PPSFM) was used to reduce the computational expense of the model and it was able to predict the NOx formation rates over the entire investigated experimental matrix with good accuracy.